2007
DOI: 10.1088/0957-4484/18/12/125205
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-dependent evolution of failure current density of highly conducting DNA-templated gold nanowires

Abstract: In this paper we report on the evolution of the failure current density as a function of diameter for highly conducting DNA-templated gold nanowires. This is explained as an increased ability of narrower nanowires to mitigate electromigration stresses, arising from an evolution of the structure of the nanowires from polygranular to bamboo-like as diameter decreases. The narrowest nanowires withstand current densities up to 3.3 × 1012 A m−2 before undergoing failure by melting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
6
18
0
Order By: Relevance
“…At higher bias, in the range of hundreds of mV, the current first saturates and upon further increase of bias voltage the wire will fail (break), as shown in Figure d. For Au‐coated NWs with 80 nm width and 30 nm gold thickness we observed the failure (destruction of the wire) at a current density of 10 11 A/m 2 , in agreement with studies of failure current on Au NWs, and roughly one order of magnitude lower than failure of Au‐coated DNA NWs on insulating substrates . We note that heat dissipation plays an important role for the failure current, and that thermal contact with a substrate allows to sustain larger current density.…”
Section: Resultssupporting
confidence: 88%
“…At higher bias, in the range of hundreds of mV, the current first saturates and upon further increase of bias voltage the wire will fail (break), as shown in Figure d. For Au‐coated NWs with 80 nm width and 30 nm gold thickness we observed the failure (destruction of the wire) at a current density of 10 11 A/m 2 , in agreement with studies of failure current on Au NWs, and roughly one order of magnitude lower than failure of Au‐coated DNA NWs on insulating substrates . We note that heat dissipation plays an important role for the failure current, and that thermal contact with a substrate allows to sustain larger current density.…”
Section: Resultssupporting
confidence: 88%
“…Investigating this phenomena is complicated by the exceedingly rapid evolution and thermal runaway that occur when the neck is narrower than about 20 nm [28][29][30][31][32][33][34][35][36][37], and by the variation in grain structure for different wires [38]. The current density at failure J F has been reported to both increase [39] and decrease [37] as the wire widths decrease.…”
Section: Prl 100 056805 (2008) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…In particular, DNA is a promising template to fabricate metal nanostructures. 2 Many studies on the metallization of DNA have been reported in the past thirteen years since the first DNA-templated nanowires were fabricated by Braun et al 3 Metal nanowires with different compositions, such as Au, [4][5][6][7][8][9][10] Ag, 3,[11][12][13][14] Cu, 15,16 Co, 17,18 Pd, [19][20][21][22][23] Pt, 24 Ni 25,26 and multiple segments, 27,28 have been created using DNA scaffolding. These studies indicate broad applicability of DNA as a template to fabricate diverse metal nanowire systems.…”
Section: Introductionmentioning
confidence: 99%